Kosztochłonność i rentowność gospodarstw indywidualnych w zależności od typu rolniczego - Felczak, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The paper presents the level of loading the different categories of agricultural production costs and profitability on farms, depending on type of farming. The study was conducted on private farms in the region “Mazowsze I Podlasie”. The research period covers the years 2004 to 2008. The variety of types of agricultural production contributed to a high level of cost charge. The reason is the low scale of production, limiting the optimization of various groups of costs and lack of modern agricultural machinery and equipment. Types of farming on a larger agricultural area were characterized by higher depreciation costs. The highest share of direct costs in total costs of the farm was characterized by intensive agricultural production.